Effect of Rhizobium trifolii peat culture on berseem mosaic virus, nodulation and nitrogen fixation in berseem - M.D. MISHRA, P.A. FUGRO and (Indian Phytopathology, 2002)
The development of berseem mosaic virus (BMV) in terms of per cent infection was comparatively higher in crop raised from Rhizobium treated seeds than in untreated. The rate of disease development 60 days after sowing (DAS) was also found to be higher in Rhizobium treated crop. Significant difference in shoot length, number and dry weight of nodules was observed within the treatments 60, 90 and 120 DAS while in case of root length significant difference among the treatments was observed 90 and 120 DAS. The number of side branches remained uniformly lower in untreated diseased plants. Mean 'fresh weight of the fodder per diseased plant in treated crop was comparatively higher than the diseased plants in untreated. The nitrogen content in roots and shoots of the healthy plants was higher than the diseased but it was comparatively lower in the leaves of the diseased plants irrespective of Rhizobium treatment. The total nitrogen content in the rhizosphere of treated healthy and diseased plants was comparatively higher than that of the untreated healthy and diseased plants, respectively.